Common Fixed Points of Four Maps Satisfying F-Contraction on b-Metric Spaces. (28th December 2017) - Nazam, Muhammad; Zhenhua, Ma; Khan, Sami Ullah; Arshad, Muhammad
Abstract : We manifest some common fixed point theorems for four maps satisfying Círíc type F -contraction and Hardy-Rogers type F -contraction defined on complete b -metric spaces. We apply these results to infer several new and old corresponding results. These results also generalize some results obtained previously. We dispense examples to validate our results.